Redefining Arctic stakeholders : integration of Asian states in Arctic law and governance - Dervovic, Medy, 1997- (2021)
Verkefnið er lokað til 11.04.2092. While most of the Circumpolar North falls under the sovereignty, sovereign rights, and jurisdiction of the eight Arctic states as the inherent Arctic stakeholders, other legitimate Arctic stakeholders emerged recently. In this regard, the integration of China, Japan, and the Republic of Korea in the ever-evolving and complex Arctic governance is of relevance to redefine the status and the role of non-Arctic states as Arctic stakeholders. Specifically, this thesis studies the means and the extent to which these three Asian states can influence the evolution of Arctic law and governance. Accordingly, the stakeholder status of Asian states is drawn from their participation in a myriad of Arctic governance processes and their Arctic interests. These interests encompass their economic and financial involvement in Arctic shipping and resource extraction, their concern over the environmental and climatic changes transforming the Arctic and impacting Asian climates at the same time, as well as their direct and indirect legal interests relevant to the Arctic. The latter are especially significant to further legitimize the recognition and enhance their stakeholder status. Notably, this is achieved by advocating for and relying on a proper implementation of international law safeguarding the legal rights of Asian states and multiplying bilateral agreements with Arctic states. For instance, through the combination of their displayed real interest in high-seas fisheries management and their legal interests under international fisheries law, they have managed to sectorally increase their status in decision-making shaping the future development of Central Arctic Ocean fisheries. Moreover, this thesis shows that Asian states could further assert their Arctic stakeholder status through their participation in the development of innovative international legal principles such as the Common Concern of Humankind to strengthen their legitimate participation in Arctic governance and facilitate their ...